SOLPS-ITER modeling of divertor scenarios for EU-DEMO. (6th September 2021) - Subba, F.; Coster, D.P.; Moscheni, M.; Siccinio, M.
Abstract: We developed a first single null divertor scenario for EU-DEMO with the SOLPS-ITER code, including all charge states of D, He and Ar in the simulation and kinetic analysis of the neutral gas, but still leaving out drifts. Our results suggest that a partially detached divertor condition can indeed be obtained, with a corresponding peak heat flux on targets to ≈2 MW m −2, within the expected tolerable steady-state limits. The plasma re-attaches ≈30 cm (measured along the plate) from the low field side strike point deep in the SOL, with a consequent raise in the electron temperature up to ≈16 eV outside the detached region, which requires further analysis to assess a possible role of sputtering, especially considering W self-sputtering. The plasma we developed exhibits Z eff ≈ 1.9 in the core, and a pumping speed a few hundred's m 3  s −1 to maintain steady-state; this points to the need of further studies to better characterize the He accumulation in the core region.